Biometria de frutos e sementes, estresses abióticos na germinação e produção de mudas de mofumbo (Combretum leprosum Mart.) - Leal, Caio César Pereira (2017)
The mofumbo (Combretum leprosum Mart. (Combretaceae)) is a shrub used for medicinal purposes, reforestation and recovery of degraded areas, with the objective of obtaining information about biometry, germination and seedling production of this species on the influence of abiotic stresses. Therefore, four research actions were developed at the Federal Rural Semi-Arid University, Mossoró - RN, from August 2014 to December 2015. For the action I, the biometric characterization was performed with a sample of 100 mature fruits of mofumbo, individually evaluated for length and thickness (fruit and seed), fresh matter mass and hectolitric weight of the seeds. The seeds were still classified according to the physical aspect in: a) intact (normal, without apparent damage); B) damaged by insect and c) malformed. In the second action, the effect of water stress on seed germination was analyzed. For this, the paper towel substrate was moistened with solutions of polyethylene glycol at osmotic potential levels: 0.0; -0.1; -0.2; -0.3 and -0.4 and -0.5 MPa under the temperatures of 25, 30, 35 and 20-30 ° C. The following characteristics were analyzed: germination, germination speed index, root and hypocotyl length, root and hypocotyl dry mass. For action III, the effect of salinity on seedling emergence, using coconut fiber as substrate and aqueous solutions of sodium chloride (NaCl), calcium chloride (CaCl2) and potassium chloride (KCl), was analyzed. In the following electrical conductivities: 0,5, 1,5; 2.5; 3.5; 4,5; 5.5 and 6.5 dSm-1. The variables analyzed were germination, germination speed index, root length and dry mass of the root and hypocotyl. The experimental design for Actions II and III was the completely randomized, with four replicates of 25 seeds each. In the research action IV, the production of seedlings with different percentages of water retention capacity of the substrate constituted by 100, 80, 60, 40 and 20% was evaluated using a randomized block with 4 replicates of 12 plants. The seedlings were submitted to water regimes 40 days after sowing (DAS). At the end of 90 days, the following evaluations were made: stem diameter, plant height, dry mass of plants, leaf area, height / diameter ratio and Dickson index. The decrease of the water potential has a negative effect for all variables analyzed, with a maximum tolerance level of -0.4Mpa, for all temperatures studied. Mofumbo seedlings show sensitivity to the three types of salts studied, with a moderate tolerance to saline solutions of CaCl2. The field capacity of around 70% was more efficient for the production of mofumbo seedlings as well as the use of field capacity below 40% and above 80% drastically reduces the development of plants